Author Correction: Hippocampus-driven feed-forward inhibition of the prefrontal cortex mediates relapse of extinguished fear. (September 2018) - Marek, Roger; Jin, Jingji; Goode, Travis; Giustino, Thomas; Wang, Qian; Acca, Gillian; Holehonnur, Roopashri; Ploski, Jonathan; Fitzgerald, Paul; Lynagh, Timothy; Lynch, Joseph; Maren, Stephen; et al.
In the version of this article initially published, the traces in Fig. 1j and in Fig. 1k, right, were duplicated from the corresponding traces in Fig. 1c, bottom, and Fig. 1d, bottom right. The error has been corrected in the HTML and PDF versions of the article.